China’s experience in organizing and managing the national science and technology program and suggestions for Vietnam - Hai, Ha Cong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
In Asia, China is one of the countries that formed a national science and technology (S&T) program quite early (the early 1980s). National S&T programs are used by the Chinese Government as an important tool to organize the implementation of S&T activities and to apply S&T research results to life and production. The implementation results of national S&T programs have made outstanding contributions to S&T development, economic development, and enhancing the competitiveness of Chinese enterprises. This article shares some experiences of China in organizing and managing the national S&T program, thereby drawing suggestions for Vietnam in organizing and managing the national S&T program in the coming period. Code: 21062801